Genotyping of Toxoplasma gondii: the advantages of variable number tandem repeats within coding regions - Moretta, Rosalia Ester (2018)
Toxoplasma gondii is an intracellular protozoan which is widely distributed. Infection occurs as a result of ingestion of uncooked meat and exposure to cat feces. Immunocompetent individuals are generally asymptomatic, while severe disease may occur in immunocompromised subjects and in congenital toxoplasmosis, which is caused by transplacental acquisition of T. gondii. Genetic diversity of T. gondii has often been studied using a PCR-RFLP scheme based on nine molecular markers. These studies led to the description of a clonal population structure with three main lineages (I, II and III) in North America and Europe and higher genetic diversity in South America. The aim of this study was to develop molecular markers that could allow the discrimination of genetic variants within each clonal lineage. We analyzed the genome of T. gondii to identify genes containing variable number tandem repeats (VNTRs). The coding sequences of T. gondii ME49 genome were processed with Tandem Repeat Finder software. A panel of candidate markers was selected based on the following parameters: the repeat unit size (>9 bp) and composition (to avoid single and dinucleotide runs), the number of copies (<20), and the absence of introns within the repeat region. The selected panel of eight molecular markers was analyzed in PRU and RH strains. As a first step, the variability of the sequence size allowed us to differentiate PRU from ME49 (two type II strains) and RH from GT1 (two type I strains). Additionally, amplification products from PRU and RH strains were sequenced to study intra-lineage variability. Aside from size polymorphisms in the amplification products we were able to identify sequence variability in polymorphic markers.